2017
DOI: 10.1080/19460171.2017.1282377
|View full text |Cite
|
Sign up to set email alerts
|

Whose input counts? Evaluating the process and outcomes of public consultation through the BC Water Act Modernization

Abstract: Public consultation has become an increasingly common form of democratic engagement. While critics have challenged the potential for public consultation to democratize policy-making due to existing power structures, few studies have undertaken a systematic evaluation of the policy outcomes of consultation. This study combines qualitative and quantitative techniques to systematically analyze participants' responses to policy proposals, and compare those responses with resulting policies. We utilized this approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In BC, ontological representations are conditioned by and inseparable from the policies, legal frameworks, and institutions of settler colonialism, many of which engage with water as a resource that can be secured for current and future (human) needs. While space constraints here prevent a comprehensive discussion of these processes, elsewhere scholars have drawn attention to the ongoing effects of the imposition of English common law doctrine and its political-legal legacies in relation to water, particularly for First Nations (see: Sam and Armstrong, 2013;Simms et al, 2016) and including the way in which it shapes contemporary water governance reforms (such as the BC Water Sustainability Act; see: Jollymore et al, 2017). While attention to these issues is important, here we focus on questions of ontological difference rather than the assertion rights within established legal frameworks.…”
Section: Hydro-ontological Contestation In Bcmentioning
confidence: 99%
“…In BC, ontological representations are conditioned by and inseparable from the policies, legal frameworks, and institutions of settler colonialism, many of which engage with water as a resource that can be secured for current and future (human) needs. While space constraints here prevent a comprehensive discussion of these processes, elsewhere scholars have drawn attention to the ongoing effects of the imposition of English common law doctrine and its political-legal legacies in relation to water, particularly for First Nations (see: Sam and Armstrong, 2013;Simms et al, 2016) and including the way in which it shapes contemporary water governance reforms (such as the BC Water Sustainability Act; see: Jollymore et al, 2017). While attention to these issues is important, here we focus on questions of ontological difference rather than the assertion rights within established legal frameworks.…”
Section: Hydro-ontological Contestation In Bcmentioning
confidence: 99%
“…Despite our prior submission stating that First Nations must be in full partnership with other jurisdictions with an interest in water governance, this approach still continues to be ignored. [105] Scholarly analysis of the provincial government's multi-stage consultation process on the WSA concluded that the public consultation model used was incapable of addressing the specific concerns of Indigenous communities and privileged existing rights holders [106]. Even if the provincial government was not willing to acknowledge the unique status of Indigenous communities within a prior allocation water regime, First Nations governmental standing within the Canadian state warrants treatment within the WSA as a government-to-government relationship that is qualitatively different than any other water user or stakeholder.…”
Section: Example: Groundwater Licensing Under the Water Sustainabilitmentioning
confidence: 99%
“…The inverted economics of communicating also means that many perspectives now compete for influence in policymaking. With this growth in channels and content, engagement processes now have the added burden of attempting to make sense of the flood of content coming through this range of channels (Jollymore, McFarlane, and Harris ). While the use of Twitter hashtags was promoted in the open government and electoral reform cases, the electoral reform committee vigorously debated the role that citizens, participating through Twitter, should play in their deliberations .…”
Section: The Profound Shifts Of the Digital Eramentioning
confidence: 99%